Herman Bavinck's Reformed eclecticism: On catholicity, consciousness and theological epistemology. Issue 3 (8th August 2017) - Brock, Cory; Sutanto, Nathaniel Gray
Abstract: This article argues that Herman Bavinck's organic worldview allows him to use classical and modern thinkers in an eclectic yet theologically principled manner. To vindicate this claim, the article observes Bavinck's self-conscious comments regarding the task of Reformed catholicity, his use of Schleiermacher and Augustine to construct a theological account of self-consciousness, and his resituating of Thomistic motifs within an organic framework in his epistemology. In so doing, the article suggests that Bavinck's catholicity is broader than previously observed, thus generating a different way of interpreting Bavinck's use of thinkers who are often thought to be in tension.